2022
DOI: 10.1172/jci.insight.142843
|View full text |Cite
|
Sign up to set email alerts
|

Anti–PD-L1 and anti-CD73 combination therapy promotes T cell response to EGFR-mutated NSCLC

Abstract: Treatment with anti–PD-1 and anti-PD-L1 therapies has shown durable clinical benefit in non–small cell lung cancer (NSCLC). However, patients with NSCLC with epidermal growth factor receptor (EGFR) mutations do not respond as well to treatment as patients without an EGFR mutation. We show that EGFR-mutated NSCLC expressed higher levels of CD73 compared with EGFR WT tumors and that CD73 expression was regulated by EGFR signaling. EGFR-mutated cell lines were significantly more resistant to T cell killing compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 54 publications
3
46
0
Order By: Relevance
“…Analysis of all common sequence (447 genes) and chromosomal (genome-wide) variants was notable for a significant positive correlation between CD73 protein expression (by IHC) and EGFR amplification (p = 0.029) (Fig. 5B), consistent with the link we identified between CD73 expression and the EGFR-associated AC-like state in scRNA-seq data from adult glioblastoma as well as reports of EGFR-mutated NSCLC expressing higher levels of CD73 compared with EGFR wild-type tumors 59,60 . In a large independent cohort of glioblastoma from the TCGA, we also found a statistically significant positive correlation between EGFR and CD73 expression (p = 0.039).…”
Section: Cd73 Expression Correlates With Oncogenic Signaling and Clin...supporting
confidence: 86%
See 1 more Smart Citation
“…Analysis of all common sequence (447 genes) and chromosomal (genome-wide) variants was notable for a significant positive correlation between CD73 protein expression (by IHC) and EGFR amplification (p = 0.029) (Fig. 5B), consistent with the link we identified between CD73 expression and the EGFR-associated AC-like state in scRNA-seq data from adult glioblastoma as well as reports of EGFR-mutated NSCLC expressing higher levels of CD73 compared with EGFR wild-type tumors 59,60 . In a large independent cohort of glioblastoma from the TCGA, we also found a statistically significant positive correlation between EGFR and CD73 expression (p = 0.039).…”
Section: Cd73 Expression Correlates With Oncogenic Signaling and Clin...supporting
confidence: 86%
“…Nevertheless, glioblastoma tumor growth was reduced in CD73-null mice with combined inhibition of CTLA-4 and PD-1 checkpoints 34 suggesting a potential benefit of combined inhibition of extracellular purinergic pathway and checkpoint pathways. A similar benefit of combined anti-CD73/anti-PD1 therapy has been observed in models of EGFR-mutated NSCLC 59 , and early-stage clinical trials 57,58 , suggesting that CD73 inhibition may provide additional complementary or synergistic therapeutic benefits with other immunotherapies.…”
Section: Discussionsupporting
confidence: 54%
“…Further, lower CD8 + TIL levels were related to EGFR mutation. EGFR mutations can upregulate CD73 expression, increase Treg numbers, and stimulate conversion of ATP into immunosuppressive adenosine, contributing to cancer progression and metastasis [ 8 , 84 , 85 ]. Increased activation of Tregs mediated by adenosine and accumulation of MDSCs, along with lower anticancer activities of natural killer cells and DCs, increased macrophage polarization toward the M2-phenotype, and inhibition of the effector T-cell-mediated response collectively led to tumor immune escape [ 86 ].…”
Section: Role Of Tme In Lung Cancer Evolution and Prognosismentioning
confidence: 99%
“…Consistently, the authors observed an increase in expression levels of genes involved in inflammation and T-cell function in tumors treated with a combination of anti-PD-L1 and anti-CD73 antibodies. These results indicate that a combination of anti-CD73 and anti-PD-L1 therapies may be effective in treating EGFR-mutated NSCLC [ 84 ].…”
Section: Role Of Tme In Lung Cancer Evolution and Prognosismentioning
confidence: 99%
“…However, induction of counter-regulatory factors such as CD73, which generates the immunosuppressive metabolite adenosine, may suppress tumor immunogenicity (22), particularly in EGFR-mutated NSCLC (23,24). Human CD73 is encoded by NT5E, which is located on the long arm (q) of chromosome 6.…”
Section: Introductionmentioning
confidence: 99%